Corrosion Behavior of Ferritic/Martensitic Steels CNS-I and Modified CNS-II in Supercritical Water - YANG, Ying; YAN, Qing-zhi; YANG, Ya-feng; ZHANG, Le-fu; GE, Chang-chun (Journal of iron and steel research, international, 2012)
The corrosion behaviors of CNS-I and modified CNS-II were evaluated by exposing to superciritical water （SCW） at 550℃ and 25 MPa with a dissolved oxygen concentration of 200× 10 ^-9 for up to 1 000 h. Detailed corrosion results of these two alloys were provided, including the growth rate of the oxide scales, microstructure of the oxide scales, distribution of phases and alloying elements. The mass gains of CNS-I and modified CNS-II were 609.73 mg/dm2 and 459.42 mg/dm2 , respectively, after exposing to SCW for 1 000 h. A duplex oxide scale with an outer porous magnetite layer and an inner relatively dense magnetite/spinel-mixed layer was identified on CNS-I and modified CNS-II after the test. The oxide scales were rather porous at the beginning of the test but the porosity decreased with increase of the exposure duration. It was found that Fe was enriched in the outer oxide layer, Cr was enriched in the inner oxide layer and O existed at a very high concnetration in the whole oxide scale. Other alloying elements such as Mo, W, Mn were depleted from the outer oxide layer and showed slightly enrichment in the inner oxide layer. The distributution of Ni was different from other elements, it was enriched in the interface bewteen the base metal and the oxide scale and depleted in the outer and inner oxide layers.